Close Reduction and Percutaneous K-wire Fixation without Image Intensifier in Supracondylar Fracture of Humerus in Children - Mohammad, Ruhullah; Shah, Sanjay Kumar Ranjan; Singh, HR; Sinha, KD; Barua, Dipan; Irshad, Mohammad; Gupta, Sanjay (Nepal Orthopaedic Association Journal, 2013)
Introduction: Extension Type III supracondyla fractures of the humerus is most common fractures around the elbow in children. Closed reduction and percutaneous pinning under image intensifier guide has been the gold standard method of treatment. However, image intensifier is not readily available in most part of our country. Closed reduction and percutaneous pinning is possible even without image intensifier. we report our case series of 51 cases who underwent closed reduction and percutaneous pinning without image intensifier. Methods: Between November 2009 and April 2011 a total of 51 children with a displaced supracondylar fractures of the humerus were managed by close reduction and percuteneus k-wire fixation without using image intensifier. They were followed for a period of minimum 6 months up to one and a half years (average one year) and the final outcome was assessed using functional and cosmetic criteria used by Flynn and associates. Results: Of these 51 patients, 46 (90%) patients showed an excellent results. Satisfactory results were achieved in 4 (8%) patients, poor in 1(2%) patients. Conclusion: Close reduction and percutaneous K-wire fixation without using image intensifier is radiation free, cost effective and relatively safe method of management of displaced supracondylar fractures of humerus in children. It can be used in a remote hospital where the facilities of image intensifier or portable x-ray are not available. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9321 Nepal Orthopedic Association Journal 2013 Vol.3(1): 19-22